Gut-liver axis in nonalcoholic fatty liver disease (NAFLD) - Koo, Yolanda Wei Ling (Nanyang Technological University, 2023)
Nonalcoholic fatty liver disease (NAFLD) is an emerging global health threat with limited therapeutic options, highlighting an urgent need to dissect its pathogenesis. The importance of adaptive immunity in the progression of NAFLD has been increasingly acknowledged, but the exact mechanism remains incomplete. This study aimed to characterize the dynamic changes of humoral response in NAFLD and possible factors driving the immunity alteration. Using a diet-induced murine model that displays the various stages of NAFLD, we found an indispensable role of B-cells in liver immunopathology. Circulating antibodies that displayed autoaggressive characteristics were detected in the hepatic environment during the fibrosis stage. Mechanistically, autoaggressive antibodies were associated with increased CD19+CD45R+CD93- IgMhiIgDlo B-cells found in the liver, blood, and large intestine but not the spleen, suggesting that B-cell fate could be tuned by the gut microbiome. 16S rRNA metagenomics data revealed a marked increase in Firmicutes/Bacteriodota ratio in NAFLD mice. Common facultative anaerobes in the gut, namely Escherichia coli and Streptococcus spp., exhibited differential immunoreactivity in control and NAFLD mice, further supporting a microbiome-directed humoral response that may shape the autoaggressive B-cells. In conclusion, our preliminary data reveal a gut-liver crosstalk mediated by B-cells that exacerbates NAFLD.